Synthesis of bacterial cellulose by Acetobacter Xylinum sp. using watermelon rind waste for biocomposite application - Fadilah, Mohamed (2010)
Cellulose was the most abundant polymer or polysaccharide that presents as the structural component of the primary cell wall of green plants but also signify for microbial extracellular polymer. The production of cellulose by microorganism such as Acetobacter xylinum sp. was most favored by researchers because the cellulose that produced was extremely pure and had a higher degree of polymerization and crystallinity than plant cellulose. The production of bacterial cellulose was expected to fulfill the high demand of cellulose in the industry. This study was focusing more on the effect of temperature and pH in the synthesis of bacterial cellulose by Acetobacter xylinum sp. using watermelon rind juice. The value of temperature and pH that being investigated was varied from 28 °C to 32 °C and from pH 4 to pH 8 respectively. The concentration for the watermelon rind juice was fixed at 7 g/L and the culture medium was incubated at fixed condition of 120 rpm. Differ from previous studies, this study use watermelon rind waste as the high potential carbon source replacing the pure carbon sources as the substrate for the synthesis of bacterial cellulose. The results data obtained shows that the optimum condition for the Acetobacter xylinum to produce the highest yield was at temperature 30 °C and pH 6 where the amount was 8.3439 g. The FT-IR analysis proves that the gelatinous membrane that produced from the experiment is cellulose. It can be shown by the appearance of absorbance peak for the C-C bonding, C-O bonding, C-OH bonding and C-O-C bonding after FT-IR analysis. In conclusion, from the data presented in this paper shows that watermelon rind waste has a high potential as the carbon source for the synthesis of bacterial cellulose and it is possible to carry out a mass production of bacterial cellulose.